Komplikace mediastinoskopického vysetrení - Cermák, J; Fiala, P; Hytych, V; Moucková, M (Rozhledy v chirurgii, 1992)
In 1970-1990 in the Institute of Lung Diseases in Prague a total of 180 mediastinoscopies were performed. In the submitted paper the authors discuss 169 of these examinations. In this group 20 examinations were associated with a peroperative or postoperative complications, i.e. a total of 12% of the examinations. However, only in three patients, i.e. cca 1.8% from the total number serious complications were involved which were unequivocally specific for mediastinoscopy. In two instances massive haemorrhage occurred from lacerated mediastinal vessels associated with superior vena cava syndrome and in one case pneumothorax developed. All these complications were controlled by surgical intervention made in time. The most frequent complication after mediastinoscopic examination was retention of a serohaematoma in the wound--this was recorded 11 times. The cause of its development is the method of preparation and anatomical conditions in the pre- and paratracheal space. The percentage of this complication can be reduced by using active drainage of the mediastinum.
Keywords: senioři; mediastinoskopie; Mediastinoscopy; Middle Aged; mužské pohlaví; ženské pohlaví; dospělí; Humans; Adult; Female; Aged; Adolescent; lidé; Male; mladiství; lidé středního věku